High temporal resolution records of the velocity of Hansbreen, a tidewater glacier in Svalbard - Błaszczyk, Małgorzata; Luks, Bartłomiej; Pętlicki, Michał; Puczko, Dariusz; Ignatiuk, Dariusz; Laska, Michał; Jania, Jacek; Głowacki, Piotr (Earth system science data, 2024)
Monitoring changes in glacial dynamics is essential for understanding the environmental response to accelerated climate warming in the Arctic. However, geodetic surveys in polar regions continue to present considerable challenges because of the harsh environmental conditions and the polar night. This study records a 14-year-long time series (2006–2019) of global navigation satellite system (GNSS) surveys of the positions of 16 ablation stakes distributed across Hansbreen, a tidewater glacier in southern Svalbard. The measurements were conducted with an exceptionally high temporal resolution, from about 1 week to about 1 month, and covering altitudes ranging from 20 to 490 m a.s.l. The position of one stake was surveyed every day. The primary data products consist of the stake coordinates and velocities. Time series of annual and seasonal velocities are also provided. This dataset may be a subject of further studies of glacier dynamics in relation to the long-term and seasonal impact of climate change on ice flow in the region. It also offers unique material for tuning numerical models of glacier dynamics and for validating satellite-derived products such as velocity and digital elevation models. The dataset described here has been made publicly available through the Zenodo repository: https://doi.org/10.5281/zenodo.8289380 (Błaszczyk et al., 2023).